The economic effect of using biological diesel oil on railway transport - Lingaitis, Leonas P.; Pukalskas, Saugirdas (Transport, 2008)
The tests performed by the authors have shown that diesel locomotive engines efficiently operate using a mixture of diesel oil and about 40% of rapeseed oil methyl ester (RME) while their ecological and economical parameters do not differ much from those of the locomotives operating on pure diesel oil. When biodiesel is used, the pollutants released into the atmosphere by an engine are less harmful. Therefore, the respective laws of the Republic of Lithuania provide for some financial incentives and allowances to transport enterprises using biological diesel oil. The paper presents a mathematical model for determining the expenses associated with the use of biological diesel oil. First published online: 27 Oct 2010